Peran Keswadayaan dalam Upaya Mewujudkan Rumah Layak Huni (RLH) pada Program Bantuan Stimulan Perumahan Swadaya (BSPS) di Desa Kalikuning, Kecamatan Tulakan, Kabupaten Pacitan - Mutia, Farah Nur Hamidah; Setiawati, Ririt Iriani Sri; Wahed, Mohammad (Jurnal Ilmiah Wahana Pendidikan, 2023)
The high population growth rate is in line with the increasing poverty rate in Indonesia which results in the inability to meet the needs of the community for habitable housing. Pacitan Regency is one of the areas with a high poverty rate and also a lot of data on Uninhabitable Houses (RTLH). Therefore, it is necessary to have government assistance in meeting the needs of Livable Houses (RLH) for the community, especially in Kalikuning Village, which is located in Tulakan District. The government through the Self-Help Housing Stimulant Assistance (BSPS) program aims to be able to realize RLH for the people in Kalikuning Village, the implementation of this program is maximized by the role of self-help which is issued personally from the community. The purpose of this study was to determine the role of self-sufficiency in the effort to realize Livable Houses (RLH) in the Self-Help Housing Stimulant Assistance Program (BSPS) in Kalikuning Village, Tulakan District, Pacitan Regency. The method used is descriptive qualitative by conducting analysis with various research methods. The results of the study show that community self-help plays a very important role in encouraging stimulants provided by the government in an effort to create Livable Houses (RLH) for the people in Kalikuning Village so that the process of building houses can be carried out and maximum results.